Application of Mixed Reality Using Optical See-Through Head-Mounted Displays in Transforaminal Percutaneous Endoscopic Lumbar Discectomy. (16th February 2021) - Liu, Xiaoyang; Sun, Jianmin; Zheng, Meimei; Cui, Xingang
Abstract : Purpose . Mixed reality (MixR) technology merges the real and virtual worlds to produce new environments and visualizations; it is being tested for numerous minimally invasive surgical procedures. This study is aimed at evaluating the use of MixR technology using optical see-through head-mounted displays (OST-HMDs) during transforaminal percutaneous endoscopic discectomy (TPED). Methods . Forty-four patients treated with MixR-assisted TPED through OST-HMDs were compared with matched patients treated with conventional TPED (n = 43 ). In the MixR-assisted TPED group, MixR technology was used to navigate the four procedures of marking, needle insertion, foraminoplasty, and positioning of the working sheath. The clinical outcomes were evaluated based on the numerical rating scale (NRS) scores and Oswestry Disability Index (ODI) on preoperative and postoperative day 1 and at the last follow-up examination. The procedural times, radiation exposure, and eye fatigue were also recorded. All patients were followed up for at least 6 months. Results . The NRS scores and ODI were significantly improved in both groups at the last follow-up visit compared with the preoperative values (P < 0.05 ); these values were not statistically different between the groups. The operation time and radiation exposure during marking, needle insertion, and total procedure significantly decreased in the MixR-assisted TPED group compared to those in the conventional TPED group (P < 0.05 ). Unfortunately, the incidence of eye fatigue increased owing to the use of OST-HMDs in the MixR-assisted TPED group. Conclusion . This study shows the utility of MixR technology for image guidance in conventional TPED. Radiation exposure is decreased, and this technology serves as a valuable tool during the TPED procedure; however, the assistance of conventional fluoroscopy is still required.